Decoy Receptor 3 Inhibits Monosodium Urate-Induced NLRP3 Inflammasome Activation via Reduction of Reactive Oxygen Species Production and Lysosomal Rupture - Pan, Yi-Gen; Huang, Ming-Ting; Sekar, Ponarulselvam; Huang, Duen-Yi; Lin, Wan-Wan; Hsieh, Shie-Liang (Frontiers in Immunology, 2021)
Gout is a common inflammatory arthritis caused by deposition of monosodium urate (MSU) crystal in joints that activates macrophages into a proinflammatory state by inducing NLRP3-dependent IL-1 secretion, resulting in neutrophil recruitment. Soluble DcR3 is an immune modulator and can exert biological functions via decoy and non-decoy actions. Previously, we showed that DcR3 suppresses LPS- and virus-induced inflammatory responses in macrophages and promotes macrophages into M2 phenotype. In this study, we clarified the actions of DcR3 and its non-decoy action motif HSPG binding domain (HBD) in MSU crystal-induced NLRP3 inflammasome activation in macrophages and in mice. In bone macrophage-derived macrophages, THP-1 and U937 cells, we found that MSU crystals-induced IL-1 secretion and NLRP3 activation were suppressed by both DcR3.Fc and HBD.Fc. Suppression of MSU-induced NLRP3 inflammasome activation is accompanied by the inhibition of lysosomal rupture, mitochondrial ROS production, cathepsins expression and cathepsin B activity, while without affecting crystal uptake and expression of NLRP3 or pro-IL-1. In air pouch mice model of gout, MSU induced less amounts of IL-1 and chemokines secretion, an increased M2/M1 macrophage ratio, and a reduction of neutrophil recruitment in DcR3-transgenic mice which expressing DcR3 in myeloid cells. Similarly mice intravenously treated with DcR3.Fc or HBD.Fc displayed less inflammation response. These findings indicate that HBD of DcR3 can reduce MSU crystals-induced NLRP3 inflammasome activation via modulation of mitochondrial and lysosomal functions. Therefore, we for the first time demonstrate a new therapeutic potential of DcR3 for gout treatment.